Repair of a Shell Fracture in a 52-Year-Old Tortoise Using Bone and Glue Techniques - Abubakar, Nura; Buhari, Salisu; Abubakar, I.A; Yakubu, A.S; Bodinga, A.H; Shehu Zaid; Salisu Ahmad, Umar; E.I Oviawe; Malami, Bashar; Aminu, Abdulhamid; Y.B, Lawali; Bello, Faisal (Faculty of Veterinary Medicine Universitas Brawijaya, 2025)
The fractures of Tortoise’s shell, especially in tortoises like Centrochelys sulcata (African spurred tortoise), pose significant task due to the unique structure and function of their shells. Old methods such as suturing, wiring, and adhesives often have limitations, prompting the need for more advanced techniques. This study presents an innovative approach using bone patches combined with epoxy resin glue for the repair of shell fractures. A shell fracture in a 52-year-old female African spurred tortoise was treated using this method, which provided a stable and supportive environment for healing. The application of bone patches and epoxy glue not only stabilized the fracture site but also reduced the risk of complications. This technique offers a promising alternative to usual methods, potentially improving outcomes for a wide range of shell injuries in tortoise. Further research is recommended to explore the long-term effects and potential enhancements of this method.